Thermal Characteristics of Slinky-Coil Ground Heat Exchanger with Discrete Double Inclined Ribs - Teguh Hady Ariwibowo; Akio Miyara (Resources, 2020)
The slinky ground heat exchanger (GHE) is the most widely utilized horizontal-type GHE, however, this GHE has a low curvature coil. The GHE has poor thermal mixing, especially at a low flowrate. At this flowrate, the coil heat exchanger has similar performance to a straight tube heat exchanger. Discrete double-inclined ribs (DDIR) are well known for their good thermal mixing by generating a vortex in straight tubes. In this paper, a numerical analysis of thermal performance for the plain coil and DDIR coil is discussed. It was found that the thermal performance of the DDIR coil was slightly higher than that of the plain coil in laminar flow. In turbulent flow, the DDIR coil was superior to the plain coil only in the first 149-min operation. The first 60-min analysis shows that in laminar flow, the average heat transfer rate in the plain coil is 59 W/m and in the DDIR coil is 60.1 W/m. In turbulent flow, the average heat transfer rate is 62 W/m, and the plain coil is 62.3 W/m. The copper DDIR coil material produced a better heat transfer rate than that of the composite and High-Density Polyethylene (HDPE). Sandy clay has the highest heat transfer rate. The influence of ground thermal conductivity on the performance of the GHE is more dominant than convection in the DDIR coil.